2013
DOI: 10.1038/onc.2013.346
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR-150 in normal and malignant hematopoiesis

Abstract: MicroRNAs are a class of small non-coding RNAs that have been implicated to mediate gene regulation in virtually all important biological processes. Recently there is accumulating evidence showing that miR-150 has essential regulatory roles in both normal and malignant hematopoiesis and holds great potential as a therapeutic target in treating various types of hematopoietic malignancies. The purpose of this review is to summarize our current knowledge about the expression patterns, biological functions and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 66 publications
4
111
0
1
Order By: Relevance
“…Among these, microRNA-150 warranted further investigation for a number of reasons. This microRNA plays an important role in normal and malignant hematopoiesis (15). In addition, plasma (14) and cellular (16,17) microRNA-150 were both downregulated in poor prognosis CLL patients based on ZAP70 and IgHV mutational status.…”
Section: Introductionmentioning
confidence: 97%
“…Among these, microRNA-150 warranted further investigation for a number of reasons. This microRNA plays an important role in normal and malignant hematopoiesis (15). In addition, plasma (14) and cellular (16,17) microRNA-150 were both downregulated in poor prognosis CLL patients based on ZAP70 and IgHV mutational status.…”
Section: Introductionmentioning
confidence: 97%
“…Monticelli et al were the first to investigate the systematic miRNA gene profiling in hematopoietic cells, demonstrating that its profiling was different from non-hematopoietic cells (15). As an important hematopoietic cell-specific miRNA, miR-150 is mainly expressed in B-cells, T-cells and natural killer cells, and plays a critical role in the differentiation of numerous hematopoietic cell lineages, particularly in lymphocyte development and function (14,16). In addition, a recent study has identified that serum circulating miR-150 is a sensor of general lymphocyte activation and may serve as a biomarker of human lymphocyte activation in healthy and disease conditions (17).…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 99%
“…The role of miR-150 in normal and malignant hematopoiesis has been summarized in detail in a review article by He et al (14). In the present review, the functions and regulatory mechanism of miR-150 as an oncogene or tumor suppressor gene in certain solid tumors were discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al, (2014). The presence of HSCs and their exposure to hemopoietic growth factors prompt the original division and differentiation into common myeloid and lymphoid progenitors, while at least one daughter cell remains an HSC, allowing the process to continue.…”
Section: Tissuesmentioning
confidence: 99%